Monitoring and Control of a Process by SCADA via Grafcet and Ladder Diagram Programming - FAUZI, AHMAD FAIZ (Universiti Teknologi PETRONAS, 2007)
This report discusses the development of a Supervisory Control and Data Acquisition (SCADA) system for the monitoring and control of a process using Programmable Logic Controller (PLC) via Grafcet and Ladder Diagram (LD) programming. The report explains the background and several methods to program a PLC. When dealing with a PLC, Grafcet is becoming the preferable method to work with because of its easiness and the clear flow of program. In this work, the Tidal Gate Control System (TGCS) is selected as a case study to investigate the advantages and disadvantages of Grafcet over LD. A literature review to track the achievements of researchers in using Grafcet and about Grafcet have been conducted. Procedure and tools required to develop TGCS are elucidated. Results on the implementation of the project are discussed. Programming the PLC to implement the monitoring and control of TGCS via Grafcet is more convenient compared to programming via LD. The recommendations on the future works of this project are also discussed.